(untitled) (Società e diritti, 2023)
Abstract First, the paper develops a brief overview of the evolution and current structure of the NHS, to highlight its undoubted peculiarities compared to ours. Subsequently, attention is paid to the consequences of malpractice in the civil-compensatory and, above all, criminal fields. This to highlight how the strong limitation of medical liability that is recorded, in both projections, in this Country can affect the quality levels and efficiency of the healthcare offer. The objective, then, is also to provide elements in the perspective of evaluating the opportunity, with respect to the need to protect the safety of treatments, of reforms that many in Italy have long been calling for the purpose of significantly reducing the criminal liability of healthcare workers (especially through the paradigm of gross negligence), or, instead, to introduce corporate liability for malpractice.